PREDICTORS OF EARLY SURGICAL INTERVENTION IN PATIENTS WITH SEVERE ACUTE PANCREATITIS - V. V. Anishchenko (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
Background. Acute pancreatitis is an important and unsolved problem of surgery. The most important subject of discussions in the treatment of acute pancreatitis is the choice of the timing of surgical intervention. Aim. To develop clinical and diagnostic criteria for early surgical interventions in patients with severe acute pancreatitis. Materials and methods. The study consisted of two stages: a retrospective study, including an analysis of the treatment of 20 patients, operated in early terms for 2-4 days and a prospective study, including analysis of human serum samples by HPLC method. Results. We determined that intra-abdominal pressure, indicators of APACHE 11 and B1SAP scores and CRP level correlate and their peak values are indicative for early surgical intervention. Using the HPLC method we isolated the group of 13 pathological and a group of 7 normal metabolites, characteristic of severe acute pancreatitis. These are specific markers of severe acute pancreatitis. Conclusions. Early surgical intervention with persistent and progressive 1AH significantly reduces the scores of the integral scales, the level of CRP which reflects the regression of MOF phenomena and reduces the risk of adverse outcome. Using the HPLC method we showed a principal possibility of predicting severe course of pancreatitis in early periods.